Frequency and reasons for outcome reporting bias in clinical trials: interviews with trialists - Smyth, RMD; Kirkham, JJ; Jacoby, A; Altman, DG; Gamble, C; Williamson, PR (BMJ Publishing Group, 2011)
Objectives To provide information on the frequency and reasons for outcome reporting bias in clinical trials.